Working Period Relationship, Safety Knowledge, and Safety Performance among the Construction Workforce of Light Rail Transit - Gias Oktaruly Sinaga; Clariza Vioito Sinaga (Universitas Airlangga, 2022)
Introduction: Safety performance refers to an individual safety behavior that can be determined by two groups of factors, environmental and individual. Each company has its own safety performance program for its employees. The company's role in occupational health and safety is to create a positive organizational climate by implementing an occupational safety and health management system. This relates to the organization's commitment to prevent accidents and occupational diseases, and to improve the level of work productivity. This research aims to analyze the relationship between the Working Period, safety knowledge, and safety performance among the workforce of the LRT construction project. Method: This research used the quantitative research approach which emphasizes data in the form of numbers and processing by statistical methods. The research design was observational with a cross-sectional approach. The population of this research was 97 respondents who filled in the questionnaires. The independent variables were Working Period relationship and safety knowledge while the dependent variable was safety performance. Result: The results show that the Working Period has a negative relationship with safety performance. Safety knowledge has a positive relationship with safety performance. The individual characteristics of the Jabodebek LRT station construction project are based on a Working Period of < 1 year for 38 people. Conclusion: Working Period has a weak relationship with safety performance and has criteria which relate to negative relationships. However, the relationship between safety knowledge and safety performance has a positive and significant relationship because the broad knowledge of safety of the employees improves their safety performance.